Socioeconomic and demographic characteristics influencing the hesitancy and refusal of COVID-19 vaccine in Ghana - Agyemang Kwasi Sampene; Cai Li; Fredrick Oteng Agyeman; Robert Brenya (SAGE Publishing, 2023)
Background: Ghana was the first country to receive the coronavirus vaccination in West Africa from AstraZeneca or Oxford. Ghana plans to vaccinate 20 million out of the 32 million population and provide the necessary doses utilizing multilateral and bilateral agreements. As Ghana begins vaccinating its citizens, there is some skepticism about administering the coronavirus vaccine (CVV). This research aimed to analyze the socioeconomic and demographic characteristics influencing vaccine hesitancy (VH) and refusal among Ghanaians. Methods: The multinomial logistics regression model was employed to investigate the relationship between respondents' socio-demographic characteristics and VH. The research data were gathered between March to June 2021 through an online survey. Findings: The findings of this study indicated that approximately 92.75% of the 400 respondents have heard about CVV. The study suggests that less than 5% of the participants have so far received the CVV. Most of the respondents (36.8%) indicated rejecting the CVV. Interestingly, male participants [adjusted odds ratio (AOR) = 1.048; 95% confidence interval (CI): 0.532-2.063] with higher educational backgrounds (AOR = 2.11; 95% CI: 0.870-5.121) had higher odds of being CVV hesitant or refusers. Low economic class, rural settlers, unmarried individuals, and unemployed people also had higher odds of being VH or refusers. The survey also shows that most Ghanaians refused to receive the CVV because they did not trust the system to track the vaccine's side or adverse effects. Conclusion: Government can use social media platforms and other media platforms to effectively provide relevant information regarding the full benefit and risks of taking the virus.